2016
DOI: 10.1016/j.jaap.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behavior, spectroscopic study and evolved gas analysis (EGA) during pyrolysis of picolinic acid, sodium picolinate and its light trivalent lanthanide complexes in solid state

Abstract: Synthesis, characterization, and thermal behavior of light trivalent lanthanide picolinate (La-Gd, except Pm) as well as the thermal behavior of picolinic acid and its sodium salt were investigated employing elemental analysis, complexometry, differential scanning calorimetry (DSC), simultaneous thermogravimetry and differential scanning calorimetry (TG-DSC), infrared spectroscopy (FTIR), X-ray power diffractometry, and evolved gas analysis (EGA) for TG-DSC coupled to FTIR. All the synthesized compounds were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
4
5
0
Order By: Relevance
“…The understanding of the thermal and pyrolytic decomposition of heavy picolinates is essential in the event that these compounds are made into functional materials which may operate in unknown thermal environments. This work extends on our previous studies on light trivalent lanthanide picolinates [20] and reports the synthesis of heavy trivalent lanthanide (Tb to Lu) and yttrium (III) picolinates. The investigation and characterisation of these novel compounds were carried out using a range of thermoanalytical, chromatographic, spectrometric and spectroscopic techniques.…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations
“…The understanding of the thermal and pyrolytic decomposition of heavy picolinates is essential in the event that these compounds are made into functional materials which may operate in unknown thermal environments. This work extends on our previous studies on light trivalent lanthanide picolinates [20] and reports the synthesis of heavy trivalent lanthanide (Tb to Lu) and yttrium (III) picolinates. The investigation and characterisation of these novel compounds were carried out using a range of thermoanalytical, chromatographic, spectrometric and spectroscopic techniques.…”
Section: Introductionsupporting
confidence: 72%
“…Spectroscopic studies of some light-lanthanides have suggested that picolinate complex binds through the nitrogen in the pyridine ring and with the carboxylate group [20]. The same mode of coordination is observed for the dysprosium [21] and terbium [19] complexes that bind monodentatively with the carboxylate group.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The exothermic peak around 420 C indicates the bond formation when the oxidation of the organic moiety occurs. The temperature difference between the TGA-DTG and differential scanning calorimetry (DSC) incidence can be explained using reports in the literature [69][70][71] which reveal that the oxidizing atmosphere accelerates the thermal decomposition. Excluding this there is no other clear result obtained from the DTA curve.…”
Section: Pyrolysis Behavior Of Praseodymium Complexesmentioning
confidence: 99%